Building Healthy Relationships: An Evaluation of the Fourth R Curriculum with Middle School Students in Bronx, NY (2010-2012) - Cissner, Amanda B. ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study seeks to test the Fourth R curriculum, a curriculum that seeks to build relationship knowledge and skills, with a younger, urban population of middle school students in the Bronx, New York. Utilizing a randomized controlled trial design, this study tests the effectiveness of the Fourth R curriculum with seventh-grade students drawn from ten public middle schools in the Bronx, New York. A secondary quasi-experimental study seeks to examine diffusion of program impacts by comparing outcomes between students assigned to the experimental control sample and students in three comparison schools where no one received the Fourth R. The study seeks to measure program impact on five primary and three secondary domains. Primary program impact domains include: Dating violence (victimization and perpetration) Sexual harassment/assault (victimization and perpetration) Peer violence/bullying (victimization and perpetration) Sexual activity Drug and alcohol use Secondary outcomes, which are targeted by the Fourth R curriculum, but are not the core program focus, include: Perceived school safety Positive beliefs (e.g., anti-fighting/violence, rejection of gender stereotypes) Pro-social behaviors This study achieved their goals through student surveys, administrator and teacher interviews, and student focus groups.